Hand-Foot Coupling: An Advantage for Crossed Legs. (April 2019) - Pearce, Alice M.; Harvey, Joshua S.; Smithson, Hannah E.; White, Rebekah C.
It is difficult to perform distinct, simultaneous motor actions with the ipsilateral hand and foot; for example, clockwise circles with the right hand and counter-clockwise circles with the right foot. By chance, we discovered that this hand-foot coupling task is easier when seated with legs crossed. We consider various explanations. First, that there are reduced demands on the contralateral hemisphere when the motor programme of the right foot is executed on the left side of the body. Second, that the legs-crossed scenario is easier because movements are symmetrical with respect to body midline. By considering related motor actions, we conclude that neither of these explanations provides a full account. Thus, we suggest a third explanation, which is that coupling effects are reduced by virtue of increased postural stability and reduced anticipatory postural adjustments.